Aeropuerto Nacional Magdalena tensión ecológica regional (2019)
In this document we can find some topics related to the high development of rural agricultural land in the Bogotá - Girardot corridor, an analysis in which we can show the strengths and weaknesses of the sector and some approaches with possible solutions, the possible problems are formulated. presents the sector and deepens the study of each one in order to propose via this document viable solutions that can be successfully implemented. One of these solutions is the proposed airport which will implement a commercial route of, for agricultural products, for tourist areas among others.